Balancing act - Tengku Azizan, Tengku Rinafli Putra; Mohd Noor, Mohd Hezmee; Ahmad, Hafandi; Abu Hassim, Hasliza; Abd Ghani, Ahmad Afifi; Ab. Latip, Mohd Qayyum; Mohd Azmi, Amirul Faiz; Shahudin, Muhammad Syafiq; Azmi, Mohd Azri; Zakaria, Alif Aiman (Universiti Putra Malaysia Press, 2015)
Birds are always associated with symbols of freedom. This sentiment originates from the fact that birds are anatomically designed to fly and are able to manipulate space in 3 dimensions; sidewards, front to back, and up and down. Artistic impression of birds usually depicts flying movements and aerodynamic forms. Bird-themed arts often assert elements of flight patterns and graceful postures of birds perching.